Resíduos agroindustriais para enriquecimento de fertilizantes orgânicos - Menegale, Vinícius Leite de Campos [UNESP]; Leão, Alcides Lopes [UNESP]; Grassi Filho, Hélio [UNESP]; Menegale, Marcela Leite de Campos [UNESP] (EIA Energy in Agriculture, 2012)
Pyroligneous Extract (P.E.) was obtained after smoke condensation formed by wood burning for charcoal production. The aim of this study was to evaluate the quality of the organic compost produced by sugar cane straw composting added with urea and pyroligneous extract. The initial Carbon/Nitrogen (C/N) ratio was fixed at the proportion 35/1 with the straw as base material. The rates of P.E. in the final mass of windrow compost were 0%, 10%, 15%, and 20%. In order to reach the necessary quantity of nitrogen, urea was used. The experiment was installed in composting cells with 1m³ capacity in a completely randomized design with 4 replications. The pH, moisture content (at 65°C), C/N ratio, organic matter content, macronutrients (N, P, K, Ca, Mg, S) and micronutrients (Na, Cu, Fe, Mn, Zn) contents from the organic compost produced were evaluated. The organic compost which contained 20% of pyroligneous extract presented higher values of pH, organic matter, percentage of C, macronutrients and micronutrients contents. Ca concentration was reduced proportionally to the amount of the applied P.E. Higher moisture content was observed in the compost with 0% of pyroligneous extract. Final C/N ratio did not present significant difference among treatments.

O objetivo do presente trabalho foi avaliar a qualidade do composto orgânico produzido por compostagem de palhiço de cana-de-açúcar com adição de uréia e extrato pirolenhoso (E.P.), que foi obtido após processo de condensação da fumaça formada pela queima da madeira para produção de carvão vegetal. A relação Carbono/Nitrogênio (C/N) inicial das leiras foi fixada em 35/1, sendo o palhiço, o material base. As porcentagens de extrato pirolenhoso na massa final das leiras de compostagem foram 0%, 10%, 15% e 20%. Para completar a quantidade de Nitrogênio necessária utilizou-se uréia. O experimento foi instalado em células de compostagem com volume de 1 m³ em delineamento inteiramente casualizado com quatro repetições. Foram avaliados pH, teor de umidade (65°C), relação C/N, teor de matéria orgânica e teor de macronutrientes (N, P, K, Ca, Mg, S) e micronutrientes (Na, Cu, Fe, Mn, Zn) dos compostos orgânicos produzidos. O composto com 20% de E.P. apresentou os maiores valores de pH, teor de matéria orgânica, porcentagem de C e teor de macronutrientes e micronutrientes. O tratamento com 0% de E.P. apresentou a maior concentração de Ca. O maior teor de umidade (65°C) foi encontrado no composto com 0% de extrato pirolenhoso. A relação C/N final do composto não apresentou diferença significativa entre os tratamentos.
Agroindustrial residues for organic fertilizer enrichment
Keywords: Organic compost; Aerobic decomposition; Sugar cane straw; Composto orgânico; Decomposição aeróbia; Palhiço de cana-de-açúcar